Pelatihan Dasar Pengoperasian Building Information Modeling (BIM) Tekla Structures bagi Guru SMK Teknik Bangunan di Kabupaten Banyumas - Dani Nugroho Saputro; Gandjar Pamudji; Nor Intang Setyo Hermanto; Arnie Widyaningrum (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This community service activity is intended to provide knowledge updates to Building Engineering Vocational High School teachers regarding the operation of the Tekla Structures BIM, where Tekla Structures is one of the tools of BIM, especially 3D drawings, detailing and material quantity. The method used is to analyze the needs of partners, lectures, discussions, and demonstrations. The participants of the activity, apart from the Building Vocational High School teachers in Banyumas, were also attended by representatives of several Subject Course Teacher Conferences (MGMP) throughout Central Java. Based on the evaluation of the activities, as many as 88.7% of participants had understood the concept of BIM after participating in this activity, participants welcomed and enthusiastically related to the development of learning by always following technological developments, especially in the construction sector.